Primary Lymphoma of Internal Acoustic Meatus Mimicking Vestibular Schwannoma—A Rare Diagnostic Dilemma - Jayashankar, Narayan; Kodur, Swati; Patkar, Deepak; Verma, Mitusha (Journal of Neurological Surgery Reports, 2021)
Background/Setting A subject presenting with a unilateral sensorineural hearing loss and with vertigo/imbalance and a lesion of internal acoustic meatus (IAM) most often represents a vestibular schwannoma. Several alternative pathologies involving the region, with clinical and neuroradiological similarities, could lead to an error in judgement and management. Rare tumors of the IAM pose unique diagnostic difficulty. A rare case that we present here had a typical history and imaging findings suggestive of vestibular schwannoma. A primary central nervous system (CNS) lymphoma was diagnosed in later stages of brain involvement warranting a retrospective analysis of the entity.Case Summary An 80-year-old male presented with unilateral sensorineural hearing loss, vertigo, and imbalance. On imaging, he was found to have a lesion in the left internal auditory meatus, reported as a vestibular schwannoma and operated upon. Subject's condition worsened with time and a repeat imaging was suggestive of a CNS lymphoma with lesions involving bilateral cerebellum and subcortical white matrix.Conclusion To conclude, primary CNS lymphoma presenting an isolated lesion in the IAM with no other parenchymal lesions at presentation is a rare incidence; to our knowledge this is the first case of such unique presentation.
Keywords: vestibular schwannoma; internal acoustic meatus; CNS lymphoma; imaging of internal acoustic meatus lesions